PROFILE OF CREATIVE EARLY CHILDHOOD EDUCATION AND DEVELOPMENT (ECED) TEACHERS OF THE 21 CENTURY - Gilar Gandana; Dadan Nugraha; Rifki Ahmad Fauzi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2021)
This study aims to examine the profile of creative teachers in the 2I century to provide an overview of best practices. This research uses a qualitative approach (case study) with interviews and observations as data collection techniques and thematic analysis as analysis techniques. Researchers conducted research on 3 ECED teachers who already had a good track record in teaching as participants in Tasikmalaya Regency. This study shows the synchronization of interview and observation data related to the characteristics of ideal creative teachers in the 2I century. It showed the attitude of teachers who could carry out a good internalization process, understand children's characteristics, are sensitive to children's conditions, are cheerful, humorous, fun, open, knowledgeable, flexible, good at communicating, and innovative in the practice of teaching children. The findings of this study show the characteristics of teachers who can evaluate themselves to continue to make improvements in the teaching process accompanied by coaching and building a supportive work environment.